Identificacion de batericera cockerelli Sulc en el cultivo de papa (Solanum Tuberosum) parroquia Santa Martha de Cuba, Canton Tulcàn, Provincia del Carchi. - Hernàndez Rosales, Jairo Geovanny (2019)
SUMMARY By not knowing why their potato crops have fallen more than 50% of production causing many economic losses being the potato crop the main economic income of farmers, an investigation was carried out in order to identify Bactericera Cockerelli in the cultivation of the Parroquia Santa Martha de Cuba, Carchi. We proceed to make a tour of different potato crops of the parish, where you can see the damage caused by this pest, looking curled yellowish plants, aerial tubers, plants with purple tips verifying that the low production of crops is mainly Bactericera Cockerelli and for this reason we proceed to conduct a survey of 20 farmers in the area where questions are asked about the knowledge about this new plague that affects the potato crops, focused on management, control and solutions for the farmer . It is recommended to carry out an integrated management that includes sowing dates, use of certified seeds of potatoes, crop rotations, monitoring with orange or yellow traps, water traps, sampling of leaves and leaflets, if control has not been achieved, foliar applications are made with insecticides of different forms of action. Among the ingredients for the control of Bactericera Cockerelli we have the insecticides with systemic activity and to transfer, or a combination of systemic and contact products, verifying that the crop when it is in development the applications must be made from the neck of the plant towards the young shoots having a good coverage as it is known that the infestation of this pest begins on the underside of the lower leaves. Keywords: Identification, Cockerelli bacteria, potato, plant health.